Identifikasi tanaman penyerap Pb di tiga ruas jalan Kota Denpasar - Krisnandika, Anak Agung Keswari; Kohdrata, Naniek; Semarajaya, Cokorda Gede Alit (Jurnal Arsitektur Lansekap, 2019)
Plant leaf capability identification to absorb Pb in three sections of Denpasar city streets. Plant as a soft element on landscape’s road, can also function as a pollutant absorber. Plants ability to absorb pollutants, depending on their characters, especially leaves morphology and its environment. Gajah Mada, P. B. Sudirman and Letda Tantular are three roads in Denpasar City which have highly activity of human and vehicle based on their location in center of trade, education and government area. Humans in this area potentially risk of exposure to lead (Pb) of motor vehicle emissions. One solution to minimize Pb exposure to humans is to use plants that can absorb dust and Pb along those roads. Survey's result shows that the dominant plants in Letda Tantular roadside are Lagerstroemia speciosae and Samanea saman, while Plumeria rubra and Callistemon viminalis are dominant in Gajah Mada, at P. B. Sudirman, Cerbera manghas and Polyalthia longifolia are dominating. The leaf of those plants then analyzed to know their capability in accumulate dust and Pb absorption. Laboratory test showed that Lagerstroemia speciosae leaves have the best ability to absorb dust (5.80472 mg/cm2) and absorb Pb (5.04133 mg/kg). Morphology’s character of Lagerstroemia speciosae leaves is stiff, with a rough surface but not hairy. Lagerstroemia speciosae has row and dense canopies with moderate plant height, this plant roots also didn't damage roads. Therefore, Lagerstroemia speciosae is one of the proper plant to use as pollutant absorber especially on fairly large roads with dense human activities.